Implementation of Religious Character Education Levels of Madrasah Tsanawiyah Education Case Study at MTS Al-Fathimiyah Karawang - Cecep Abdullah; Amirudin; Acep Nurlaleli (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
This research aims: 1). To find out the implementation of character education at MTS Al-Fathimiyah. 2). To find out the character of religious culture at MTS Al-Fathimiyah. 3). To find out the obstacles to the implementation of religious character education at MTs Al-Fathimiyah. This research was conducted using a qualitative approach that focused on collecting data obtained from interviews, observation, documentation. Data analysis techniques using data reduction. Presentation of data, and drawing a conclusion. From the research that has been done, it can be concluded that the implementation of religious character education at MTs Al-Fathimiyah has become a culture or character of MTs Al-Fathimiyah which has been running and maintained for a long time so that it has become a hallmark of formal institutions, both junior high and fellow MTs. The culture of Islamic boarding school-based schools in the early days became something strange among students who did not attend school, but with the guidance of teachers who continued to be encouraged to become role models and the regulations that had been implemented had an impact on the success of the implementation of religious character education so that it could be imitated by other formal institutions.